TINGKAT KEPATUHAN PEMILIK SARANA APOTIK DALAM MELAKSANAKAN KEBIJAKAN PEMERINTAH TERHADAP PERSYARATAN PENGELOLAAN APOTIK DI KABUPATEN SRAGEN - VETYLIANASARI, AGRESTHA (Dinamika Hukum, 2015)
The purpose of this study is to assess analyze the factors that affect the level of compliance means of pharmacies in implementing policies to the requirements of pharmacy management This research uses juridical sociological study because it describes and gain clarity about government policy towards the management of the pharmacy. The nature of this research is descriptive analysis namely: "A study that seeks to provide an overall picture, depth, to obtain a clarity about government policy towards the management of pharmacy The results of that study factors that influence the level of compliance of the owners means of pharmacies in the implementation of government policy on pharmacy management requirements are: Knowledge Own Means pharmacists to pharmacy management provisions of Regulation fraction instead of basic health or pharmacist, but businessmen and entrepreneurs that lead to ignorance will the existing regulations. The attitude of the owner of the means pharmacies in follow-up provisions PERMENKES No. 922 1993 or KEPMENKES Decree No. 1332 / Menkes / SK / X / 2002 on the Amendment to the regulation of the Minister of Health Decree No. 922 / Menkes / Per / X / 1993. Most of the owner Means Pharmacies Pharmacies and implement compliance in accordance with the regulations of the Minister of Health Decree No. 922 / Menkes / Per / X / 1993, but there are still some small part Pharmacies and Pharmacy Facility owners who do not comply with the regulations of the Minister of Health Decree No. 922 / Menkes / Per / X / 1993, should a need to increase compliance due to internal factors, for example: the number of prescriptions or drugs that come in very little, the amount of capital that must be removed for the purposes of pharmaceuticals, revenues are not worth the expense. While external factors include: the selling price of a tight competition, increasing the number of pharmacies, consumers doubt on the quality of pharmacy services. Keywords: level of compliance, the owner of the means pharmacies, government policies, management of pharmacy